An exploration of introducing internships as an integral facet of distance learning in library and information science - Sharath, G V Krishna; Rao, T Sreenivasa (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction: This case study examines the qualitative approach to the overall process, implementation strategy, and operational complexity behind internships in Library and Information Science (LIS) programs delivered through distance education. Indira Gandhi National Open University (IGNOU), aligning with the New Education Policy (NEP) 2020. Data Collection Methods: A qualitative textual analysis was conducted on IGNOU's internship guidelines through primary and secondary data collected from the official websites, along with the author's personal experiences to provide internship insights. Data Analysis: Fundamental to this study is a textual analysis of the different aspects of the training, the essential things, and the responsibilities of the participants during their training. Results and Discussion: The internship program in LIS offers benefits like practical skills enhancement, increased employability, and application of theoretical knowledge in real-world settings. Challenges include logistical issues, student engagement, and mentor support. Conclusion: The case study explores the new LIS internship programme, emphasising its benefits, challenges, and recommendations for success. It suggests streamlined processes, student preferences, and efficient communication with governing bodies to ensure a successful program. Recommendations include clear guidelines, adequate resources, and ongoing evaluation for success.